The Emerging Soybean Production Frontier in Southern Africa: Conservation Challenges and the Role of South‐South Telecouplings. Issue 1 (12th May 2015) - Gasparri, Nestor Ignacio; Kuemmerle, Tobias; Meyfroidt, Patrick; le Polain de Waroux, Yann; Kreft, Holger
Abstract: Soybean expansion has been a strong driver of deforestation and biodiversity loss in South America (SAM). Here, we highlight strong similarities in environmental, institutional, and other contextual conditions among SAM and Southern African (SAFR) dry forest and savanna regions, and compile evidence for an emerging soybean production frontier in SAFR. Knowledge transfer, cooperation, and direct investment between SAM and SAFR countries constitute crucial elements of soybean expansion in Africa. Comparing maps of soybean suitability, biodiversity, and carbon revealed substantial and spatially diverse trade‐offs, suggesting that the emerging soybean frontier in SAFR may poses major challenges for conservation. An increased focus of conservation science on agricultural expansion and intensification in SAFR, as well as strong environmental policies for balancing agricultural production and conservation goals, are needed to mitigate potentially large trade‐offs. The coupling of production frontiers should be a vehicle for the transfer not only of agricultural technology and production models, but also of experiences in environmental governance on emerging agricultural frontiers.